Health from the roots - benefits of ginseng supplementation - Szczurek, Katarzyna; Szczepanek, Dawid; Biecka, Adrianna; Wyrzykowski, Mikołaj (Quality in Sport, 2025)
Background: Ginseng has been used in traditional Chinese medicine for thousands of years as a cure for various diseases. The term “ginseng” is a popular name for herbal drugs that are based on the roots of several distinct species of plants, mainly Korean or Asian ginseng (Panax ginseng C.A. Meyer) and American ginseng (Panax quinquefolius). In this study, we aimed to analyze the health benefits of ginseng. Materials and methods: We analyzed publications found in PubMed and Google Scholar. Articles were selected on the basis of keywords such as “ginseng’’, “Panax ginseng”, “ginsenosides”, and “health benefits”. For the final analysis, the eligible articles were published from 2010--2024. Results: All of the research findings regarding the benefits of ginseng on cognitive function are consistent with their results. Ginseng supplementation has a positive effect on cognition in humans. Seniors are the group of patients who benefit the most from ginseng. Additionally, studies have suggested positive effects on obesity, coronary disease and diabetes. Conclusions: Panax ginseng supplementation can be recommended for patients, as it seems to be relatively safe for them and has several positive effects on health. Further studies are needed to investigate the influence on human health better.